US-Singapore relations, 1965-1975 : strategic non-alignment in the Cold War - Chua, Daniel (NUS Press, 2017)
"At the height of the Cold War in Southeast Asia, the foreign relations between the United States and Singapore demonstrated the interplay between America's strategy of containment and Singapore's efforts at a non-aligned foreign policy. But there is a deeper story. American involvement in the Vietnam War not only held back the spread of communism in Southeast Asia, but also catalysed economic and strategic cooperation between the United States and Singapore. The author argues that Singapore might not have achieved its success so rapidly without the support of the US. As the war in Vietnam raged on, Singapore became a critical refueling point, also providing ship and aircraft repair for the US military. Commercial and strategic support from the United States lifted Singapore out of the economic doom predicted for the city-state after secession from Malaysia, cessation of Indonesian trade during Konfrontasi and Britain's military withdrawal. By considering the importance of the US's role in Singapore's nation-building, this book provides an important supplement to the well-trodden narrative that attributes Singapore's success to good governance."--Back cover